PENGARUH MODEL PEMBELAJARAN GUIDED INQUIRY TERHADAP HASIL BELAJAR SISWA PADA MATERI PERAWATAN MESIN SEPEDA MOTOR DI SMK NEGERI 1 KLUET SELATAN : PENGARUH MODEL PEMBELAJARAN GUIDED INQUIRY TERHADAP HASIL BELAJAR SISWA PADA MATERI PERAWATAN MESIN SEPEDA MOTOR DI SMK NEGERI 1 KLUET SELATAN - Hasiholan, Sifaima; Abubakar Dabet; Azhar Syahputra; Jumadi; Riza Andriani; Islami Fatwa (Global Action and Education for Society, 2026)
This study aims to determine the effect of the Guided Inquiry learning model on students' learning outcomes in motorcycle engine maintenance material at SMK Negeri 1 Kluet Selatan. This study uses a quantitative method with a quasi-experimental design in the form of a Nonequivalent Posttest-Only Control Group Design. The research sample consists of two classes, namely the experimental class using the guided inquiry model and the control class using the conventional method. The data collection instrument is in the form of a learning outcome test that has been tested for validity and reliability. Based on the results of the data analysis (t-test), the significance value of 0.000 < 0.05 indicates a difference in student learning outcomes on motorcycle engine maintenance material at SMK Negeri 1 Kluet Selatan between those using the Guided Inquiry learning model and those not using the Guided Inquiry model. The use of the Guided Inquiry learning model in the teaching process of motorcycle engine maintenance material, whether in individual or group learning, can provide more effective and efficient learning. Thus, the Guided Inquiry learning model has a positive effect on student learning outcomes in motorcycle engine maintenance material. This finding shows that the application of the appropriate learning model can improve the quality of education at SMK Negeri 1 Kluet Selatan.